Pelatihan Seni Tari Tradisional dalam Rangka Pendidikan Karakter Anak dan Pelestarian Budaya Bangsa - Indah Puspitasari Puspitasari; Ridha Kurniasih Astuti; Agustina Sri Hafidah (LPPM STKIP PGRI Pacitan, 2016)
Education launched the development of character axis in each subject today. Besides, preservation of national culture was also the important attention. One of them was through traditional dance. This activity, which is in the form of training, aimed at providing education and training of traditional dance in which its activities were targeted specifically at children in the elementary and kindergarten school in Kayen village Pacitan. Learning the art of traditional dance was the alternative to introduce and develop the children's knowledge of the local culture in advance instead of foreign cultures. The event was held from March to December 2016. The implementation phases of training were: (1) the preparation including the observation, the location determination and target; (2) the implementation of training (3) the evaluation and the further step including the reports on activities, evaluation and action plan. The method applied in this activity was the training with the trainer every Sunday morning. The inference of these activities was the traditional dance training was expected to provide the positive impact on children's character education and the awareness in the preservation of national culture.